Q. 15

If 𝒳 = 2 cos t – 2 cos3t, 𝒴 = sin t – 2 sin3t, show that =cot t.

Answer :

Theorem: y and x are given in a different variable that is t . We can find by finding and and then dividing them to get the required thing.


=


= cost – 6 sin2t × cost ………..(1)



= -2sint + 6cos2t × sint …………….(2)


Dividing (1) and (2), we get


=


= .


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses